Analyzing writing in english-medium instruction at university - Salaberri Ramiro, María Sagrario; Sánchez Pérez, María Del Mar (Linguarum Arena, 2015)
The number of bilingual and English-Medium-Instruction (EMI) degree programmes has grown significantly in Spanish universities during the last few years, becoming a new trend within the Bologna system. The implementation of the European Higher Education Area (EHEA) led to changes in Spanish universities, promoting a shift in the teaching methods and enhancing the improvement in quality and international competitiveness pursuing an increase in mobility opportunities and the employability of the European graduates. The command of the English language in specialized university contexts became thus crucial. Research conducted at university level reveals that university students often have difficulty in performing the cognitive and discursive operations involved in the comprehension and production of written texts. These difficulties aggravate when the written performance has to be conducted in a nonnative language. The present paper analyses the written production of Chemistry students following an EMI approach at the University of Almería (Spain) from a qualitative perspective. Results show the differences in the performance of certain areas of written language competence, which evidences the need to adopt methodologies that solve the problems and difficulties faced by students in order to help them integrate the global features of the writing ability within their own course contents in a second language.